Detection of Luminous Vibrio harveyi in Penaeid Shrimp Through Nested PCR Using Haemolysin Gene Primer - WAWAN ABDULLAH SETIAWAN; UTUT WIDYASTUTI; MUNTI YUHANA (Bogor Agricultural University, Indonesia, 2015)
Whiteleg shrimp (Litopenaeus vannamei) is one of the most important aquaculture commodity in Indonesia. However, the luminous disease primarily caused by Vibrio harveyi bacteria still becomes an obstacle in penaeid shrimp farming, especially in shrimp hatchery. This study was aimed to identify the presence of V. harveyi in L. vannamei through nested PCR using haemolysin gene primer. First, initial primers were designed using V. harveyi VIB 391 haemolysin gene sequence (accession number: DQ640264), flanking the position 133 to 756. This primer pairs were used to identify haemolysin gene in both V. harveyi MR5339 and V. harveyi 275 strain. Sequencing results from each sample showed 99% similarity with haemolysin gene sequence in Genebank. Furthermore, the sequence of V. harveyi MR5339 haemolysin gene was used to design the nested PCR primers. The first primer pairs of nested PCR have successfully amplified the haemolysin gene fragment of all V. harveyi strains samples from position 52 to 405. The second primer pairs of nested PCR have amplified position 204 to 405 where it can detect all of V. harveyi strains used as sample sources in this study. The application of nested PCR technique in this study was able to identify V. harveyi strains at serial dilution of cells density as low as 100 cfu/mL, which is equal to a single cell or at DNA concentration up to 101 fg/µL.